2008
DOI: 10.1086/590669
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunity in Healthy Adults after Parenteral Vaccination with Outer‐Membrane Vesicles fromNeisseria meningitidisSerogroup B

Abstract: Parenteral MenB vaccination selectively reprograms preexisting naturally acquired mucosal immunity. As new-generation protein-based MenB vaccine candidates undergo evaluation, the impact of these vaccines on mucosal immunity in both adults and children will need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
1
21
0
1
Order By: Relevance
“…Our findings highlight the importance of the complex interplay between humoral and cell-mediated immunity against meningococci and suggest that OMV-based vaccines have the potential to induce both Th1 and Th2 cytokines, at least as detected in cells from peripheral circulation. Natural immunity against meningococci at the systemic level has been shown to be a balanced Th1/Th2 memory response (52), whereas the mucosal T cell response has been characterized as Th1 polarized (39,44,52). Hence, the results presented here obtained with OMV vaccination are consistent with the picture seen in natural immunity in adults, at least at the systemic level.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings highlight the importance of the complex interplay between humoral and cell-mediated immunity against meningococci and suggest that OMV-based vaccines have the potential to induce both Th1 and Th2 cytokines, at least as detected in cells from peripheral circulation. Natural immunity against meningococci at the systemic level has been shown to be a balanced Th1/Th2 memory response (52), whereas the mucosal T cell response has been characterized as Th1 polarized (39,44,52). Hence, the results presented here obtained with OMV vaccination are consistent with the picture seen in natural immunity in adults, at least at the systemic level.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we have demonstrated that crossreactive T cell responses were accompanied by the production of both Th1 and Th2 cytokines measured as IFN-␥, IL-4, and IL-10. Parenteral immunization with OMV vaccines has previously been claimed to induce a Th1-biased response (40,44), but a clear association between any defined cytokine profile and protection against meningococcal disease has not yet been established. It has been suggested that a Th1-skewed immune response can be beneficial by promoting enhanced Fc␥R1 expression on phagocytes, neutrophil mobilization, and intracellular bactericidal activity, whereas a more balanced Th1/Th2 response will be necessary to secure the activation and regulation of essential B cell responses such as IgG and IgA production and opsonophagocytosis (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The paradigmatic cellular immune response to mucosal infection involves Th2-regulated IgA production; however, there are examples where Th1 or Th17 responses may be critical determinants of protective immunity against potentially invasive mucosal pathogens (12,13,23,26). Because cholera is prototypical of a noninflammatory, toxin-mediated diarrhea (17), it was plausible that the disease would induce a CD4 ϩ T-cell response skewed predominantly toward a noninflammatory Th2 response to V. cholerae antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the ratio of Th1/Th2 responses as an important determinant of the mucosal immune response (12,13,26). As shown in Fig.…”
Section: Cytokine Responses Tomentioning
confidence: 99%
“…PBMC were isolated from 45 ml peripheral venous blood, as previously described (19). Briefly, plasma was separated by centrifugation (400 3 g, 20˚C, 10 min) and discarded.…”
Section: Isolation Of Mononuclear Cellsmentioning
confidence: 99%